1997
DOI: 10.1111/j.1469-7793.1997.353bb.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin‐blockable calcium currents in rat ventricular myocytes; a third type of cardiac cell sodium current

Abstract: Whole‐cell patch clamp currents from freshly isolated adult rat ventricular cells, recorded in external Ca2+ (Ca2+o) but no external Na+ (Ma4o), displayed two inward current components: a smaller component that activated over more negative potentials and a larger component (L‐type Ca2+ current) that activated at more positive potentials. The smaller component was not generated by Ca2+ channels. It was insensitive to 50 μm M2+ and 10 μm La3+, but suppressed by 10 μm tetrodotoxin (TTX). We refer to this componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 40 publications
7
87
0
Order By: Relevance
“…Based on the different effect of STX and TTX on L-type calcium channel, it is plausible that L-type calcium channels may bear a binding site for STX, but not for TTX. A different channel-mediated current, the TTX-blockable calcium current (I Ca,(TTX) ), has been reported in human atrial (Lemaire et al, 1995) and ventricular (Gaughan et al, 1999) myocytes, in guinea pig (Cole et al, 1997) and rat (Aggarwal et al, 1997) ventricular cells, and in neural preparations (Meves and Vogel, 1973;Akaike and Takahashi, 1992). The identity of the channel that conducts I Ca(TTX) is still controversial; however, it is possible that I Ca(TTX) is mediated by a subtype of a sodium channel and not a calcium channel (Aggarwal et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the different effect of STX and TTX on L-type calcium channel, it is plausible that L-type calcium channels may bear a binding site for STX, but not for TTX. A different channel-mediated current, the TTX-blockable calcium current (I Ca,(TTX) ), has been reported in human atrial (Lemaire et al, 1995) and ventricular (Gaughan et al, 1999) myocytes, in guinea pig (Cole et al, 1997) and rat (Aggarwal et al, 1997) ventricular cells, and in neural preparations (Meves and Vogel, 1973;Akaike and Takahashi, 1992). The identity of the channel that conducts I Ca(TTX) is still controversial; however, it is possible that I Ca(TTX) is mediated by a subtype of a sodium channel and not a calcium channel (Aggarwal et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, in unpublished observations, we found that TTX did not significantly alter human PASMC E m (-41.2±2.6 mV, -46.2±3.1 mVin TTX, n=4, data not shown) indicating that Na + channel activity does not modulate E m in cultured normal human PASMC. [19] and triggers either further Ca 2+ release from the sarcoplasmic reticulum (SR) (causing contraction) or replenishes SR Ca 2+ pools by SERCA-mediated Ca 2+ re-uptake [1,29]. iii) TTX-sensitive Na + channels can conduct Ca 2+ ions in the absence of extracellular Na + or in the presence of trace doses of steroids such as ouabain and digoxin [6,29]; this can contribute to local and global Ca 2+ signaling, especially in heart failure patients treated with digoxin [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ re-uptake [1,29]. iii) TTX-sensitive Na + channels can conduct Ca 2+ ions in the absence of extracellular Na + or in the presence of trace doses of steroids such as ouabain and digoxin [6,29]; this can contribute to local and global Ca 2+ signaling, especially in heart failure patients treated with digoxin [29].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…It is, however, worthwhile to note that T-type channel expression was induced by growth hormone treatment in the experiments of Piedras-Renteria et al 17 By contrast, with the absence of T-type current in adult human heart, an LVA calcium current was first reported in human atria, 18 sharing some typical properties with sodium channels such as TTX sensitivity (designated ICa TTX ). Its description in rat 19 and guinea pig 20 myocytes indicated that it is not exclusively observed in diseased human cells. The study of Heubach et al 21 in this issue of Circulation Research demonstrates for the first time the coexistence of ICa TTX with ICa T in guinea pig ventricular myocytes.…”
mentioning
confidence: 99%